En Bloc Liver Kidney Transplantation Using Donor Splenic Artery as Inflow to the Kidney: Report of Two Cases. Issue 10 (6th July 2016) - Gunabushanam, V.; Clendenon, J.; Aldag, E.; Chadha, M.; Kramer, D.; Steers, J.; Sahajpal, A.
Abstract : The number of simultaneous liver–kidney transplants has been increasing. This surgery is associated with an increased risk of complications, longer duration of surgery and longer ischemia time for the renal allograft. Two patients listed for liver–kidney transplant at our center underwent en bloc combined liver–kidney transplantation using donor splenic artery as inflow. Patient 1 previously underwent cardiac catheterization that was complicated by a bleeding pseudoaneurysm of the right external iliac artery that required endovascular stenting of the external iliac artery and embolization of the inferior epigastric artery. Patient 2 was on vasopressor support and continuous renal replacement therapy at the time of transplant. In this paper, we described a novel technique of en bloc liver–kidney transplant with simultaneous reperfusion of both allografts using the donor splenic artery for renal inflow. This technique is useful for decreasing cold ischemia time and total operative time by simultaneous reperfusion of both allografts. It is a useful technical variant that can be used in patients with severe disease of the iliac arteries. Abstract : En bloc simultaneous liver–kidney transplant using donor splenic artery for renal inflow is a feasible option in select situations.